2012
DOI: 10.1142/s0217732312501106
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Isgur–wise Function and Its Derivatives Within a Heavy–light QCD Quark Model

Abstract: In determining the mesonic wave function from QCD inspired potential model, if the linear confinement term is taken as parent ( with columbic term as perturbation ), Airy's function appears in the resultant wave function -which is an infinite series. In the study of Isgur-Wise function (IWF) and its derivatives with such a wave function, the infinite upper limit of integration gives rise to divergence. In this paper, we have proposed some reasonable cut-off values for the upper limit of such integrations and s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 26 publications
(38 reference statements)
1
19
0
Order By: Relevance
“…It measures the overlap of the wave functions of the light degrees of freedom in the initial and final mesons moving with velocities v and v respectively. The calculation of Isgur-Wise function is non-perturbative in principle and is performed for different phenomenological wave functions for mesons [11,21]. This function depends upon the meson wave function and some kinematic factor, as given below :…”
Section: Slope and Curvature Of Isgur-wise Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…It measures the overlap of the wave functions of the light degrees of freedom in the initial and final mesons moving with velocities v and v respectively. The calculation of Isgur-Wise function is non-perturbative in principle and is performed for different phenomenological wave functions for mesons [11,21]. This function depends upon the meson wave function and some kinematic factor, as given below :…”
Section: Slope and Curvature Of Isgur-wise Functionmentioning
confidence: 99%
“…We introduce u(r) = rR(r) and the dimensionless variable ρ(r) = (2µb) The unperturbed wave function [21] for ground state is 6) where N 0 is the normalization constant and The first order perturbed eigen function ψ (1) can be calculated using relation (A.6).…”
Section: A Appendixmentioning
confidence: 99%
See 1 more Smart Citation
“…We have developed an approximate analytic ground state wave function of meson with Coulomb plus linear potential. In analogy to our previous works [15][16][17], here also we have studied the IWF of heavy-light mesons with this wave function. Regarding slope and curvature of IWF ( Table-1), we find that our results becomes better for heavier mesons.…”
Section: Conclusion and Remarksmentioning
confidence: 96%
“…In this paper, we propose a simpler form of analytic solution of Schrodinger equation with Cornell potential. Our earlier work with Cornell potential using perturbation technique [15][16][17]72,73], considering its linear confinement term as parent, we have found that Airy's infinite polynomial function appears in the solution for wave function. Based upon our past study, here we construct the analytic form of the meson wave function for linear plus Coulombic potential in terms of Airy's function.…”
Section: Introductionmentioning
confidence: 99%